Strategi Pemasaran dalam Upaya Meningkatkan Tingkat Hunian Kamar di Labuan Sundai Resort - Dihan Sintia; Hendri Azwar (Jurnal Ilmiah Dan Karya Mahasiswa, 2024)
The writing of this thesis aims to find out the marketing strategies in an effort to increase room occupancy rates at the Labuan Sundai Resort. The approach used in this research is descriptive qualitative with SWOT analysis. Interviews, observations and documentation were used for the data collection process. There were 3 respondents from resort employees, and 3 respondents from guests staying at the resort. The research results showed that Labuan Sundai Resort attracts guests with beautiful views, exciting activities and complete packages. However, limited electricity, small room sizes and limited access are obstacles. Promotion via social media and sales calls is effective, but requires expanding the strategy. Building facilities and promotions with influencers can increase attractiveness, even though the threat of competitors, overpricing and natural conditions still exists.